Paternal body mass index and offspring DNA methylation: findings from the PACE consortium. (29th January 2021) - Sharp, Gemma C; Alfano, Rossella; Ghantous, Akram; Urquiza, Jose; Rifas-Shiman, Sheryl L; Page, Christian M; Jin, Jianping; Fernández-Barrés, Silvia; Santorelli, Gillian; Tindula, Gwen; ,
Abstract: Background: Accumulating evidence links paternal adiposity in the periconceptional period to offspring health outcomes. DNA methylation has been proposed as a mediating mechanism, but very few studies have explored this possibility in humans. Methods: In the Pregnancy And Childhood Epigenetics (PACE) consortium, we conducted a meta-analysis of coordinated epigenome-wide association studies (EWAS) of paternal prenatal body mass index (BMI) (with and without adjustment for maternal BMI) in relation to DNA methylation in offspring blood at birth (13 data sets; total n = 4894) and in childhood (6 data sets; total n = 1982). Results: We found little evidence of an association at either time point: at all CpGs, the false-discovery-rate-adjusted P -values were >0.05. In secondary sex-stratified analyses, we found just four CpGs for which there was robust evidence of an association in female offspring. To compare our findings to those of other studies, we conducted a systematic review, which identified seven studies, including five candidate gene studies showing associations between paternal BMI/obesity and offspring or sperm DNA methylation at imprinted regions. However, in our own study, we found very little evidence of enrichment for imprinted genes. Conclusion: Our findings do not support the hypothesis that paternal BMI around the time of pregnancy is associated with offspring-blood DNA methylation, even at imprinted regions.